Correlation of non-esterified fatty acids with acute coronary syndrome risk in young Chinese adults - Wu, Jian-di; Luo, Jian-jing; Li, Jia-huan; Hao, Sha-li; Wang, Wen-li; Li, Wu; Li, Wei-wen; Huang, Guo-lin; Liang, Guo-quan; Wen, Wei-xing; He, Wei-min; Liu, Yang-guang; et al. (Frontiers in Endocrinology, 2025)
ObjectiveCirculating non-esterified fatty acids (NEFAs) are linked to endothelial dysfunction and coronary artery disease (CAD) mainly in older adults. This study examines the association between NEFAs and acute coronary syndrome (ACS) risk in young Chinese individuals.MethodOf the 1264 young ACS patients and 1072 age-matched controls aged 55 years or younger assessed, 1108 ACS patients and 979 controls were found eligible. Their conventional cardiovascular risk factors were compared, and serum NEFA levels were determined using a commercial assay kit.ResultACS patients exhibited a higher prevalence of male sex, smoking, hypertension, diabetes and overweight/obesity compared to controls. Additionally, ACS patients had elevated levels of low-density lipoprotein cholesterol, triglycerides, and NEFAs, along with reduced levels of estimated glomerular filtration rate and high-density lipoprotein cholesterol (all P < 0.05). After adjusting for various cardiovascular risk factors through multivariate logistic regression, NEFA levels remained independently associated with ACS risk in young patients (per 100 µmol/L increase, OR = 1.207, 95% CI = 1.163–1.253). Restricted cubic spline analysis confirmed a linear relationship between NEFA levels and ACS risk. Furthermore, receiver operating characteristic analysis indicated that NEFA levels have significant diagnostic value for ACS in young patients, with an area under the curve of 0.62 (P < 0.001).ConclusionElevated circulating NEFA levels could be linked with increased ACS risks in young Chinese individuals, regardless of traditional cardiovascular risk factors.